ENGLISH MATERIAL DEVELOPMENT BASED ON SCIENTIFIC APPROACH: A CONTENT ANALYSIS OF “WHEN ENGLISH RINGS A BELL” COURSE BOOK - Elok Putri Nimasari (Universitas Muhammadiyah Surakarta, 2016)
Government has launched the 2013 curriculum four years ago. It becomesone of interests to be investigated. Pros and cons have been raised toward thisnew implemented curriculum. In 2014, a revision of the 2013 curriculum coursebook entitled “When English Rings the Bell” had been done. A content analysisstudy is needed toward the implementation of the 2013 curriculum for the sake ofmaterial development. This study aims to investigate whether or not the revisedof the 2013 curriculum course book entitled “When English Rings a Bell” is inline with the theory of scientific approach. This study used qualitative descriptivemethod to describe the results.